Language matters. Addressing the use of language in the care of people with diabetes: position statement of the English Advisory Group. Issue 12 (28th November 2018) - Cooper, A.; Kanumilli, N.; Hill, J.; Holt, R. I. G.; Howarth, D.; Lloyd, C. E.; Kar, P.; Nagi, D.; Naik, S.; Nash, J.; Nelson, H.; Owen, K.; et al.
Abstract: The language used by healthcare professionals can have a profound impact on how people living with diabetes, and those who care for them, experience their condition and feel about living with it day‐to‐day. At its best, good use of language, both verbal and written, can lower anxiety, build confidence, educate and help to improve self‐care. Conversely, poor communication can be stigmatizing, hurtful and undermining of self‐care and can have a detrimental effect on clinical outcomes. The language used in the care of those with diabetes has the power to reinforce negative stereotypes, but it also has the power to promote positive ones. The use of language is controversial and has many perspectives. The development of this position statement aimed to take account of these as well as the current evidence base. A working group, representing people with diabetes and key organizations with an interest in the care of people with diabetes, was established to review the use of language. The work of this group has culminated in this position statement for England. It follows the contribution of Australia and the USA to this important international debate. The group has set out practical examples of language that will encourage positive interactions with those living with diabetes and subsequently promote positive outcomes. These examples are based on a review of the evidence and are supported by a simple set of principles. What's new?: The use of language by healthcare professionals can have a profound impact on people living with diabetes. Our working group, which represents people with diabetes and key stakeholders, has developed a set of principles to guide healthcare professionals, with the goal of improving interactions with those living with diabetes.